Improved neuroprotection with melatonin-augmented hypothermia versus hypothermia alone in a perinatal asphyxia model. (7th June 2011) - Faulkner, S; Chandrasekaran, M; Bainbridge, A; Kelen, D; Powell, E; Price, D; Cady, E; Golay, X; Raivich, G; Robertson, N J
Abstract : Background: Melatonin (N-acetyl-5-methoxytryptamine) is a naturally occurring hormone, an anti-oxidant and cellular pro-survival factor. It is used safely in children with sleep disorders. Beneficial properties of melatonin following brain injury in adult animals have been observed. It is unknown if melatonin augments hypothermic neuroprotection in the developing brain. Proton magnetic resonance spectroscopy (MRS) biomarkers (e.g., lactate/N acetyl asparate – Lac/NAA) are surrogate outcome markers in asphyxiated infants and correlate with cell death. Aim: To determine whether melatonin-augmented hypothermia is more neuroprotective versus hypothermia alone in a piglet model of perinatal asphyxia. Methods: 17 male piglets (<24 h) underwent transient global hypoxia-ischaemia and were randomized to (1) 24 h hypothermia (33.5°C) 2–26 h; or (2) 24 h hypothermia plus 5 mg/kg melatonin infusion started 10 min after resuscitation and 24 h thereafter. 1H MRS (Lac/Creatine (Cr), NAA/Cr and Lac/NAA) in the thalamus (vmFB) and dorsal subcortical white matter voxels were acquired up to 48 h after injury. Area under the Curve (AUC) levels were calculated. Results: Compared to hypothermia alone, post-insult treatment with melatonin combined with hypothermia led to a significant decrease in thalamic Lac/NAA and Lac/Cr AUC (p<0.05, one-sided t-test) in the deep grey matter and increase in NAA/Cr (p<0.05) in the white matter (figure 1 ). Discussion: Combined cooling with melatonin was more neuroprotective than cooling alone in this piglet perinatal asphxya model. Melatonin is a promising candidate for adjunct therapy with cooling in newborn infants with moderate to severe neonatal encephalopathy and may reduce adverse outcome.